2005
DOI: 10.1088/0268-1242/20/9/009
|View full text |Cite
|
Sign up to set email alerts
|

Novel low cost chemical texturing for very large area industrial multi-crystalline silicon solar cells

Abstract: Multi-crystalline silicon surface etching without grain-boundary delineation is a challenging task for the fabrication of high efficiency solar cells. The use of sodium hydroxide-sodium hypochlorite (NaOH-NaOCl) solution for texturing a multi-crystalline silicon wafer surface in a solar cell fabrication line is reported in this paper. The optimized etching solution of NaOH-NaOCl does not have any effect on multi-crystalline silicon grain boundaries and it also has excellent isotropic etch characteristics, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 18 publications
(17 reference statements)
0
12
0
Order By: Relevance
“…The mc ‐Si wafer consists of a lot of millimeter‐sized single crystals of various grain orientations, and can also form the micrometer‐sized pyramid textures under an anisotropic alkali etching. However, the normal of pyramids (<100>) and etching rate of indivual single crystal depend on its oritentation, resulting in remarkably different microstuctures between mc ‐Si and sc ‐Si wafers (see Supporting Information S1) . Fortunately, the above results have shown that the nanosized pseudo‐pyramid texture can be formed on the surface of mc ‐Si wafers.…”
Section: Approach and Mechanism To Nanoscale Pseudo‐pyramid Textured mentioning
confidence: 86%
“…The mc ‐Si wafer consists of a lot of millimeter‐sized single crystals of various grain orientations, and can also form the micrometer‐sized pyramid textures under an anisotropic alkali etching. However, the normal of pyramids (<100>) and etching rate of indivual single crystal depend on its oritentation, resulting in remarkably different microstuctures between mc ‐Si and sc ‐Si wafers (see Supporting Information S1) . Fortunately, the above results have shown that the nanosized pseudo‐pyramid texture can be formed on the surface of mc ‐Si wafers.…”
Section: Approach and Mechanism To Nanoscale Pseudo‐pyramid Textured mentioning
confidence: 86%
“…Therefore, the (100)‐oriented grains have a dark appearance owing to the excellent light‐trapping ability of the upward pyramids, the (111)‐oriented grains appear shiny because of the strong light reflection of the nearly reclined pyramids, and the (110)‐oriented grains have a gray appearance because of the moderate light‐trapping ability of the tilted pyramids. The average reflection of the DRE mc‐Si wafer is more than 30%, and such high reflection loss is the main reason why alkali etching is incapable of texturing the mc‐Si wafer …”
Section: Resultsmentioning
confidence: 99%
“…By changing deposition conditions, the optical properties of DLN film can be varied over a wide range. The substrates used were boron doped NaOH-NaOCl polished multicrystalline silicon (mcSi) wafers [8].…”
Section: Methodsmentioning
confidence: 99%